Experimental and numerical analysis of iso-octane/ethanol sprays under gasoline engine conditions. (May 2015) - Keller, P.; Knorsch, T.; Wensing, M.; Hasse, C.
Abstract: High pressure sprays under gasoline engine conditions are studied in a high pressure/high temperature constant volume chamber using a combined experimental and numerical approach. Both pure iso-octane and ethanol as well as their mixtures are considered. The aim of this work is to investigate the differences between the single component sprays and to identify how the spray structure changes for multicomponent fuels. Especially the influence of the azeotropic behavior of iso-octane/ethanol mixtures on the differential evaporation and the resulting vapor formation is considered. Experimental techniques include Phase-Doppler Anemometry (PDA), shadowgraphy and Schlieren measurements and results are reported for the droplet size distribution, the liquid and the vapor distribution, respectively. The numerical investigations use both a single droplet model as well as 3D spray simulation. In both numerical approaches, the thermodynamic description of the vapor–liquid equilibrium (VLE) at the droplet surface takes into account non-ideal effects for multicomponent mixtures. Liquid activity coefficients are described using the non-random two-liquid (NRTL) approach. First, the results for pure iso-octane and ethanol sprays for two operating points are presented with good agreement between numerical and experimental results. The differences in penetration between the two fuels are discussed. Afterwards, two binary iso-octane/ethanol mixtures, E10 and E85, respectively, are investigated for the same two operating points as for the pure component fuels. Starting from single droplet studies, the differential evaporation behavior is discussed especially with respect to the thermodynamic model. The influence of the azeotrope on droplet evaporation is investigated in detail and significant differences are found for the components' volatility. The resulting differences in the differential evaporation behavior are quantified using two factors, the differential evaporation and the separation factor, respectively. Using the same thermodynamic model, results from the full 3D simulation for the two mixtures are presented. The resulting fuel vapor distributions and the liquid compositions are analyzed and the influence of the azeotrope is discussed. The differential evaporation and separation factor are presented and it is shown that they are both suitable for quantitative analysis since their values are directly comparable between the single droplet and the 3D spray simulation.